Menyusun Proyeksi Pendidikan, Metode, dan Aplikasi Proyeksi Sekolah Dasar Tahun 2012/2013-2020/2021 - Ida Kintamani Dewi Hermawan (Badan Standar, Kurikulum, dan Asesmen Pendidikan, Kemendikbudristek, 2014)
The purpose of this study is to provide an overview how to make projections of education, what method to use, and its application in the form of the projection results primary school from 2012/2013 to 2020/2021. The method used is the study documentation on data owned and required in compiling the projections. The population was used extensively at the national level. The results show that education is needed to compile data and projections of population, education data for several years, the educational indicators and assumptions. The projection method used is the number of entries is rough and current students. In addition, the results of the primary school projection is three things, i.e. a projection of students, projection of educational infrastructure, projection of human resources. The result of the projections of primary school students in the year 2020/2021 is 33,908,350, new entrants become 5,832,046, and graduates into 4,973,548, as well as APK of 119.57% and APM 96.19%. Based on the projection of the elementary level student then needed school of 185,052, class of 1,271,104, and classrooms of 492,016 so that the required additional per year amounted to 10,456 rooms per year. Furthermore, the principal of primary school required of 2,643 per year, while teachers 55,093 per year.ABSTRAK Tujuan penulisan ini adalah memberikan gambaran tentang bagaimana menyusun proyeksi pendidikan, metode apa yang digunakan, dan aplikasinya dalam bentuk hasil proyeksi sekolah dasar dari tahun 2012/2013 sampai tahun 2020/2021. Metode yang digunakan adalah studi dokumentasi tentang data yang dimiliki dan yang diperlukan dalam menyusun proyeksi. Populasi digunakan secara menyeluruh di tingkat nasional. Hasilnya menunjukkan bahwa untuk menyusun proyeksi pendidikan diperlukan data dan proyeksi penduduk, data pendidikan selama beberapa tahun, indikator pendidikan, dan asumsi. Metode proyeksi yang digunakan adalah angka masukan kasar dan arus siswa. Selain itu, hasil proyeksi sekolah dasar ada tiga, yaitu proyeksi siswa, proyeksi prasarana pendidikan, dan proyeksi sumber daya manusia. Hasil proyeksi siswa tingkat SD tahun 2020/2021 sebesar 33.908.350, siswa baru menjadi 5.832.046, dan lulusan menjadi 4.973.548 serta APK sebesar 119,57% dan APM sebesar 96,19%. Berdasarkan proyeksi siswa tingkat SD diperlukan sekolah sebanyak 185.052, kelas sebanyak 1.271.104, dan ruang kelas sebanyak 492.016, sehingga diperlukan tambahan sebanyak 10.456 ruang per tahun. Selanjutnya, kepala sekolah tingkat SD yang dibutuhkan sebanyak 2.643 per tahun, sedangkan guru sebanyak 55.093 per tahun.